The Distortion of American Dream as Reflected in Dreiser’s Sister Carrie - Yulmiati, . (TELL - US JOURNAL, 2015)
The writer concerns to analize the distortion of American dream as reflected in Sister Carrie  that influenced by the social condition of America at the end of nineteenth century. The writer uses historical and sociological approach in analzinng the data. The primary data were taken from the novel itself and the secondary data, historical background and sociological aspects, were taken from other resources. From historical approach, the writer reviews the context of the time dealing with the story in the novel. From sociological approach, the writer studies about  the social condition of America at the end of 19th century that influnced the story in the novel. Sister Carrie is the story of a naive girl who live as the mistress of a man who fell in the social scale as she rose to her success as an actress. From this novel, the writer found that the effect of social changing influnced to American character in getting their dream. This condition were strongly seen in the character of Carrie and Hurswood, as the main characters of this novel. Both of them ignored the Contending of American Dream (equality, commonwealth, community, and generosity). Meanwhile, it was explaied by American Statements as the guidance to get the dream.